COVID-19 and productivity-enhancing digitalisation: Firm-level evidence from Slovenia - Borowiecki, Martin (OECD Economics Department Working Papers, 2023)
This paper provides evidence on the impact of digitalisation on productivity in Slovenia during the COVID-19 crisis. The pandemic affected overall labour productivity negatively. Nonetheless, results show that firms that were more ICT-intensive before the pandemic experienced a smaller decline in their labour productivity growth compared to their less ICT-intensive peers in the same 2-digit level sector. This resilience effect was strongest for firms that are integrated in global value chains. A second finding is that COVID-19 resulted in productivity-enhancing reallocation of labour to ICT-intensive firms, reflecting that these firms registered higher employment growth relative to their less ICT-intensive peers during the pandemic. A third finding is that high levels of state ownership in a sector was associated with less productivity-enhancing reallocation. This suggests that state-owned enterprises retained workers that could be redirected to more productive firms. Together, these findings highlight the potential of digitalisation to support resilience and stronger productivity growth, although labour market rigidities and state ownership hamper the positive impact of digitalisation